Anti-PD-1 immune-related adverse events are associated with high therapeutic antibody fixation on T cells - Gazzano, Marianne; Parizot, Christophe; Psimaras, Dimitri; Vozy, Aurore; Baron, Marine; Abbar, Baptiste; Fallet, Vincent; Litvinova, Elena; Canellas, Anthony; Birzu, Cristina; Pourcher, Valérie; Touat, Mehdi; et al. (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICI) widely improved the treatment of solid and hematologic malignancies. Yet, a remarkable proportion of patients receiving ICI develop immune related adverse events (irAEs) which are difficult to define as treatment-related. This underlines the need to develop a biomarker to guide irAE diagnosis. We developed a novel flow cytometry assay combining measurement of anti-PD-1 (programmed cell death protein-1) occupancy and evaluation of remaining PD-1 receptor availability with anti-IgG4 PE and anti-PD-1 BV421. We prospectively collected blood and biological fluids samples from patients treated by IgG4 anti-PD-1 therapy (nivolumab or pembrolizumab), with (n=18) or without (n=12) current irAE. We analyzed PD-1+ and IgG4+ staining pattern and MFI values of these parameters on CD4 and CD8 T cells, and IgG4+/PD-1+ MFI ratios are calculated. A higher mean fluorescence intensity IgG4+/PD-1+ ratio was measured on peripheral CD4+ T cells of irAE cases, when compared to controls (p=0.003). ICI-related toxicity is therefore associated with increased therapeutic antibody occupancy of PD-1 receptors on CD4+ T cells. Furthermore, in one case of ICI-related pneumonitis, binding of therapeutic antibody was stronger on lung CD4+ T cell than in blood. In another case of ICI-related encephalitis, the PD-1 receptor occupancy was total on CSF CD4 T cells, but only partial on peripherical CD4 T cells. Our results suggest that flow cytometry monitoring of ICI occupancy can be used in patients treated with monoclonal ICI to guide irAE diagnosis.